Putin acts, Taiwan reacts [Taiwan's greenhouse reduction plans]. - Yu-Tzu Chiu (IEEE spectrum)
Russia's ratification of the Kyoto protocol on climate change has sent ripples around the world, with effects being felt especially in places where emissions trading systems are being established. Russia's accession to the agreement means that the protocol takes effect this year, requiring signatory states to reduce their greenhouse gases back to below 1990 levels by 2012. The effect of Russia's action are also being felt in some unlikely places, such as Taiwan, which is not even a party to the Kyoto pact. Since Taiwan's most successful exporting industries are major producers of greenhouse gases, Premier Shyi-kun Yu upgraded an operating task force to formulate policies on greenhouse reduction.